Long term productivity of a ley farming system in the 'secano interior' of central Chile - Pozo A. del; Ovalle C. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Pasture dry matter production and wheat yield were evaluated in a rotation of 3 years of a pasture legume (Medicago polymorpha) following 1 year of wheat (i.e. a ley farming system), over 8 years (1984 - 1991). Liveweight gains of sheep were also assessed the last 4 years. Biomass production of the pasture legumes ranged between 4.6 - 7.8, 2 - 11, and 4.2 - 8.6 ton ha-1 of dry matter, in the first, second and third year after the wheat crop. Wheat grain yield fluctuated between 2.2 and 4.5 ton ha-1, and animal production was on average 248 kg ha-1 of liveweight, which represent 2 to 5 times greater for both commodities than in the traditional local system based on a wheat/fallow rotation without annual legumes.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)